Type II Agency Issues And Firm Value: The Case Of Nigerian Public Listed Companies - Salihi, Adamu Awaisu (2024)
The prevalence of Type II agency problem has led to the expropriation of minority interest right which reduces the firm value. Therefore, type II agency problems have been identified as some of the key factors that led to the collapse of many companies. Hence, its regulation becomes necessary especially in an emerging market where there is weak governance structure. Thus, this study examined the influence of type II agency variables (family, board, and concentrated ownership structures) on firm value of Nigerian public listed companies. The study also examined the conditions that lead expropriation of minority interest rights, thereby reduces the firm value of public listed companies in Nigeria. The study went on to investigate how expropriation of minority interest can be mitigated and improve the firm values of Nigerian public listed companies.